Heydər Əliyev 10 İllik Yubiley Kitab Sərgisi : Fədəkərlıq, Liderlik, və İlham dolu əsrin təntənəsi = Heydar Aliyev Centennial Book Fair : Celebrating a Century of Dedication, Leadership, and Inspiration - ADA University Library (ADA University, 2023)
International Book, Science and Culture holiday dedicated to the 100th anniversary of National Leader Heydar Aliyev.
Keywords: ADA University.; ADA University -- Book fair.; ADA University -- Aliyev, Heydar -- Centennial.